Improving collaboration between native Hawaiians and energy professionals to explore geothermal energy potential in Hawai‘i - Kamana, Noa; Vaughan, Mehana (Frontiers in Sustainability, 2024)
Climate change is threatening vulnerable geographies including island nations, posing major economic and social risks. The development of renewables, specifically geothermal energy in the Hawaiian archipelago offers promising possibilities to achieve energy independence and security. However, geothermal development faces opposition from the Native Hawaiian community, stemming from Hawaiian cultural identity and beliefs that natural resources are akua (Gods). Throughout Hawaiʻi’s history Native Hawaiians have been marginalized in decision making processes, overlooking cultural implications of development. In this article we explore how to improve collaboration with Native Hawaiians to guide future geothermal energy development in Hawaiʻi. We conducted seven semi-structured interviews with individuals from three groups: (1) Native Hawaiians community members, (2) Native Hawaiian geothermal professionals, and (3) non-native geothermal professionals. Using a grounded theory approach, we discovered the interviews emphasized the status of geothermal development, feelings towards geothermal, perceived obstacles, knowledge gaps and recommendations to improve development. Interviews were manually transcribed and analyzed to identify similarities and differences in responses. Due to the limited number of interviews, our results are not statistically robust, but do offer insights for equitable culturally grounded geothermal energy development. Findings include six key themes. 1) Renewable energy is critical for Hawaiʻi’s future sustainability. (2) The primary obstacles facing geothermal energy expansion are not cultural. The largest obstacles are regulatory and financial. (3) Reasons and opportunities to support Geothermal exploration and expansion exist. Geothermal provides Hawaiʻi a firm energy resource with a minimal ecological footprint. (4) Cultural implications surrounding geothermal are significant. (5) There is a need to rebuild collaboration and trust. Past developments failed to collaborate with local communities, destroying trust. (6) Opportunities to improve social / environmental justice and benefits for native/local communities forced to host green energy projects. Interview were then coded based on these overarching themes, extracting related text using Microsoft Excel. The information from this research allowed us to produce a narrative synthesis detailing areas of conflict and knowledge gaps and allowed us to create recommendations to improve collaboration between energy professionals and Native Hawaiians. This research has implications to guide potential green energy development in indigenous communities across the world.